THE ISTIHSAN METHOD AND ITS ARGUMENT IN THE PRACTICE OF ISLAMIC ECONOMICS - Tehedi Tehedi (CV. ADIBA AISHA AMIRA, 2025)
The main sources of Islamic law are the Qur'an and the Hadith of the Prophet. The model for seeking Islamic law must first go through the legal verses found in the Qur'an, after which explanations are sought in the Hadith or the Sunnah of the Prophet. However, in this era of modern economics, there are many new systems or concepts of economic transactions that need to be examined to determine whether these systems or transactions can be conducted according to Islamic law. Seeing this reality, the usuli furu'iyah scholars, who usually come from the Hanafi or Maliki schools, seek new methods that can ensure the law functions well and serves the welfare of humanity. The approach taken was to apply the method of qiyas khafi based on maslahat. This method was then named the istihsan method. This research uses a normative approach with empirical descriptive analysis. The results of this research conclude that the istihsan method is one of the best ways for a mujtahid to discover and establish a legal ruling. Moreover, its application can be carried out in economic transactions that did not exist or had never been conducted before, even though the istihsan method still has its pros and cons. With the application of the ihtihsan method in legal discovery in the field of modern economy today, new laws are produced that are more suitable and provide benefits for the needs of society, and in turn, can avoid stagnation